Evaluasi Maturitas Manajemen Keberlanjutan Bisnis pada Perusahaan Konstruksi Besar di Indonesia - Nurhadi, Didik; Wiguna, 1 Putu Artama (Jurnal Aplikasi Teknik Sipil, 2024)
The construction industry in Indonesia faces numerous disruptions, such as supply chain issues, regulatory changes, and natural disasters. Understanding the sector's preparedness for these disruptions is vital for economic and industrial resilience. This research assesses the Business Continuity Management (BCM) maturity of large Indonesian state-owned (BUMN) and private (BUMS) construction companies using an empirical model based on ISO 22301 and NFPA 1600, combined with the pairwise comparison of Analytical Hierarchy Process (AHP) for weighting factors. The maturity value is derived from the ratio of the maximum achievable score “4” to the sum product of the weighting and scores for the relevant criteria, where scores range from "0" indicating the lowest level of effort or no effort, to "4" indicating the highest level of compliance. The focus on large companies is due to their capacity to implement BCM initiatives. The analysis reveals that the effectiveness of Business Continuity Management (BCM) is driven by several key attributes. Prioritizing efforts on "Risk Assessment," "Top Management Commitment," "Performance Objectives," and "Business Impact Analysis" enables organizations to achieve a substantial level of maturity. Findings show that Indonesian large construction companies have improved their BCM maturity, scoring 66.16% (moderate progress).